The Jurisprudence of Noise: An Islamic Legal Analysis of the “Sound Horeg” Phenomenon in Indonesia - Ahmad Nabilul Maram; A’azliansyah Farizil Anam; Ramatoulaye Senghore (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2025)
The phenomenon of sound horeg as a form of excessive and competitive contemporary cultural expression has raised theological, social, and ethical issues that urgently need to be studied scientifically. This practice is not merely entertainment, but has shifted to become a symbol of luxury and public arrogance that has social, medical, and moral implications. This research is important because there has been no comprehensive legal-theological study that systematically assesses this phenomenon from an Islamic legal perspective. Using a qualitative and interpretive theological-legal approach, this study combines the taḥqīq al-manāṭ method (empirical investigation of factual reality) with Mustafa Muslim's inductive thematic interpretation, which interprets verses of the Qur'an through keyword analysis and the context of revelation. The synthesis of the interpretation results is then integrated with the principles of uṣūl al-fiqh and maqāṣid al-sharī‘ah, especially lā ḍarara wa lā ḍirār, to produce a contextually relevant legal analysis. The results of the study show that sound horeg, in its current form, fundamentally contradicts the principles of Islamic ethics and law because it contains elements of wastefulness (isrāf and tabdzīr), public harm (ḍarar), immoral entertainment (lahw al-ḥadīth), and social arrogance (kibr). These findings confirm that Islamic jurisprudence has adequate methodological tools to navigate modern phenomena without losing its normative values, while opening opportunities for the development of a constructive cultural ethical model that is in line with the objectives of Sharia. REFERENCES 'Asyur, Muhammad Thohir bin.